SCOT: a comparison of cost-effectiveness from a large randomised phase III trial of two durations of adjuvant Oxaliplatin combination chemotherapy for colorectal cancer - Robles-Zurita, José Antonio; Boyd, Kathleen A.; Briggs, Andrew H.; Iveson, Timothy; Kerr, Rachel; Saunders, Mark P.; Cassidy, Jim; Hollander, Niels Henrik; Tabernero, Josep; Segelov, Eva; Glimelius, Bengt; Harkin, Andrea; et al. (Springer Nature, 2018)
BACKGROUND: The Short Course Oncology Therapy (SCOT) study is an international, multicentre, non-inferiority randomised controlled trial assessing the efficacy, toxicity, and cost-effectiveness of 3 months (3 M) versus the usually given 6 months (6 M) of adjuvant chemotherapy in colorectal cancer. METHODS: In total, 6088 patients with fully resected high-risk stage II or stage III colorectal cancer were randomised and followed up for 3–8 years. The within-trial cost-effectiveness analysis from a UK health-care perspective is presented using the resource use data, quality of life (EQ-5D-3L), time on treatment (ToT), disease-free survival after treatment (DFS) and overall survival (OS) data. Quality-adjusted partitioned survival analysis and Kaplan–Meier Sample Average Estimator estimated QALYs and costs. Probabilistic sensitivity and subgroup analysis was undertaken. RESULTS: The 3M arm is less costly (-£4881; 95% CI: -£6269; -£3492) and entails (non-significant) QALY gains (0.08; 95% CI: −0.086; 0.230) due to a better significant quality of life. The net monetary benefit was significantly higher in 3M under a wide range of monetary values of a QALY. The subgroup analysis found similar results for patients in the CAPOX regimen. However, for the FOLFOX regimen, 3M had lower QALYs than 6M (not statistically significant). CONCLUSIONS: Overall, 3M dominates 6M with no significant detrimental impact on QALYs. The results provide the economic case that a 3M treatment strategy should be considered a new standard of care.
Keywords: Cancer - Tratamiento; Economic evaluation; colorectal cancer; treatment duration